RIGID GAS PERMEABLE USAGE IN AMBLYOPIC PATIENTS: IS IT SECURE ENOUGH? Poster Presentation - Case Report - Resident - Septian Dwi Prabowo; Christina Aritonang (Majalah Oftalmologi Indonesia, 2023)
Introduction : Amblyopia and anisometropia are frequently diagnosed during preschool. Several treatments approaches are currently being prescribed to reduce myopia progression, such RGP. Case Illustration : A-17-years-old-patient came with blurry vision in both eyes since elementary school. Since Junior High School patient always felt un-comfort using spectacles and routinely check for 6 months. Initial visual acuity was 2/60 pinhole 5/30 and 4/60 pinhole 5/12 in the right and left eye. The previous spectacles were S-4.75 C-1.50 A0 become 5/20 and S-9.00 C-3.50 A0 become 5/6.5 in the right and left eye. After correction S-11.00 C-4.00 A180 become 5/6.5 and S-9.00 C-3.50 A0 become 5/6.5. Due to high myopia, RGP contact lenses were fitted. RGP contact lenses that are given to this patient were BC 8.10 mm/P -9.00D/ D 9.2mm in right eye, and BC 8.00 mm/ P -8.50D/ D 9.2mm in left eye, and visual acuity become 5/6.5 in both eyes. Discussion : Management of anisometropia can be accomplished through a variety techniques. In cases of severe anisometropia, contact lenses are frequently utilized for refractive correction such as RGP, that is produced in a larger variety of powers, can fit in a certain base curve or diameter, has high oxygen permeability, improved durability, increased contrast sensitivity, and correct higher corneal astigmatism and decreased amblyopia Conclusion : The risk-benefit and patients' low compliance haven't yet provided a definitive answer. RGP contact lens is secure and practical in the treatment of anisometropia and amblyopic patients. All of which are crucial for achieving the greatest vision and comfort possible following adaptation.